Citizens' Preferences Toward Halal Products - Ma'arif, Bambang Saiful; HMZ, Nandang; Arif, M. Fauzi (KnE Social Sciences, 2023)
The purpose of this article is to explore people’s enjoyment of halal products and the various ways in which this pleasure is manifested. The research utilized a quantitative approach employing the Theory of Persuasion and a questionnaire as the data collection technique. The study involved 486 respondents who are residents of Bandung Regency. The findings of the research are as follows: 1. Consumers’ perception that halal products are healthy contributes to their pleasure in using these products. 2. Pleasant experiences with halal products foster loyalty among consumers, encouraging them to remain loyal to the products. A significant majority of citizens, 347 respondents (74.1%), expressed agreement with their fondness for halal products and demonstrated an eagerness to seek further information about them. Additionally, 67 respondents (14.3%) expressed a strong agreement with their preference for halal products. Keywords: preferences, halal products, da’wah persuasion, ELM-based da’wah